The impact of culinary tourism on tourist satisfaction and destination loyalty: Padang city, West Sumatra context - Fitrizal Fitrizal; Elfiswandi Elfiswandi; Sigit Sanjaya (Jurnal Manajemen dan Pemasaran Jasa, 2021)
The objective of this study to identify the impact of culinary tourism on tourist satisfaction and destination loyalty. Respondents in this study are the tourists in Padang city, West Sumatra. The study utilized primary data which is obtained through the questionnaire. The respondents were selected by convenience sampling method. The number of respondents is 384 determined by using Lemeshow formula. Data were analyzed by Path Analysis. The result show that culinary tourism has a positive and significant effect both on destination loyalty and tourist satisfaction. Tourist satisfaction has a positive and significant effect on destination loyalty. Culinary tourism is one of the effective tools to increase tourism. Tourist satisfaction will be achieved with components of culinary tourism. Tourist satisfaction even though insufficient category, it will be able to increase loyalty.